Increased attention to the tobacco power wall predicts increased smoking risk among adolescents. (January 2019) - Martino, Steven C.; Setodji, Claude M.; Dunbar, Michael S.; Shadel, William G.
Abstract: The purpose of this correlational study was to evaluate the association between attention paid by adolescents to the tobacco power wall and their susceptibility to future smoking. The study was conducted in the RAND Store Lab (RSL), a life-sized replica of a convenience store designed to investigate how tobacco advertising displays in retail point-of-sale environments relate to tobacco use risk and behaviors. In this study, middle and high school students ( N  = 80) shopped in the RSL while their attention to the tobacco power wall was measured covertly. Before and after shopping in the RSL, participants completed a measure of susceptibility to smoking in the future. Controlling for baseline cigarette smoking susceptibility and other potential confounders, attention toward the tobacco power wall was found to be significantly associated with future smoking susceptibility, p  = .046. This finding suggests that policies aimed at decreasing the prominence of power walls in retail outlets should be given careful consideration as ways to reduce the impact of point-of-sale tobacco advertising and promotion on youth smoking susceptibility. Highlights: This study evaluated the association between attention paid by adolescents to the tobacco power wall and their susceptibility to future smoking Attention toward the tobacco power wall was found to be significantly associated with future smoking susceptibility This finding suggests that policies aimed at decreasing the prominence of power walls in retail outlets should be given careful consideration